2017
DOI: 10.1002/cbic.201700257
|View full text |Cite
|
Sign up to set email alerts
|

Photometric Characterization of the Reductive Amination Scope of the Imine Reductases from Streptomyces tsukubaensis and Streptomyces ipomoeae

Abstract: Imine reductases (IREDs) have emerged as promising enzymes for the asymmetric synthesis of secondary and tertiary amines starting from carbonyl substrates. Screening the substrate specificity of the reductive amination reaction is usually performed by time-consuming GC analytics. We found two highly active IREDs in our enzyme collection, IR-20 from Streptomyces tsukubaensis and IR-Sip from Streptomyces ipomoeae, that allowed a comprehensive substrate screening with a photometric NADPH assay. We screened 39 car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Enzymatic approaches represent a promising alternative: Amine transaminases give the primary β‐chiral amine in a DKR directly, as demonstrated in the synthesis of niraparib or pregabalin . Additionally, IREDs and reductive aminases have been explored for the one‐step asymmetric synthesis of secondary or tertiary amines from ketones . Until now, these reductive aminations have been investigated only to prepare α‐chiral amines.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Enzymatic approaches represent a promising alternative: Amine transaminases give the primary β‐chiral amine in a DKR directly, as demonstrated in the synthesis of niraparib or pregabalin . Additionally, IREDs and reductive aminases have been explored for the one‐step asymmetric synthesis of secondary or tertiary amines from ketones . Until now, these reductive aminations have been investigated only to prepare α‐chiral amines.…”
Section: Methodsmentioning
confidence: 99%
“…In previous works we and others demonstrated that simple achiral aldehydes are converted by IREDs and reductive aminases (RedAms; this subgroup of IREDs catalyze imine formation directly in the active site rather than using the pre‐formed imine out of the reaction solution and are hence especially efficient in reductive amination because they require only stoichiometric amounts or a small excess of the amine nucleophile substrates). Employing the IRED from Streptomyces ipomoeae , aliphatic aldehydes are converted with similar efficiency or outperform the reaction with the model substrate cyclohexanone with some amine nucleophiles such as pyrrolidine.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, IREDs have rapidly assumed an important role as highly stereoselective catalysts for amine synthesis. [18][19][20][21][22][23][24] IREDs strictly require NADPH and are preferentially used in cellular systems, which makes them very suitable for application in photosynthesis-driven whole-cell biotransformations.…”
mentioning
confidence: 99%